2005
DOI: 10.1242/jcs.02303
|View full text |Cite
|
Sign up to set email alerts
|

Increased keratinocyte proliferation by JUN-dependent expression of PTN and SDF-1 in fibroblasts

Abstract: In skin, fibroblasts of the connective tissue play a decisive role in epidermal homeostasis and repair by contributing to the regulation of keratinocyte proliferation and differentiation. The AP-1 transcription factor subunit JUN plays a crucial role in this mesenchymal-epithelial interplay by regulating the expression of two critical paracrine-acting cytokines, keratinocyte growth factor (KGF) and granulocyte-macrophage colony-stimulating factor (GM-CSF). We have performed gene expression profiling of wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
3
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 46 publications
6
92
3
6
Order By: Relevance
“…Since JUN gene is involved in cell proliferation and differentiation, AMR-induced down-regulation may be advantageous for inhibition of tumor growth. 45 In short, microarray data showed that the antitumor effect of AMR is through its regulatory effects on functional genomics targeting the apoptotic process. The house keeping gene glyceraldehyde-3-phosphate dehydrogenase (G3PDH) gene was used as control.…”
Section: Discussionmentioning
confidence: 99%
“…Since JUN gene is involved in cell proliferation and differentiation, AMR-induced down-regulation may be advantageous for inhibition of tumor growth. 45 In short, microarray data showed that the antitumor effect of AMR is through its regulatory effects on functional genomics targeting the apoptotic process. The house keeping gene glyceraldehyde-3-phosphate dehydrogenase (G3PDH) gene was used as control.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 has been identified as an inducing factor in these coculture experiments (96,97). Conversely, factors secreted by fibroblasts influence the growth and differentiation of keratinocytes, indicating reciprocal cellcell interaction (98). Additionally, ECM context has an important impact on fibroblast cellular identity.…”
Section: Extrinsic Factors Governing Fibroblast Cellular Identitymentioning
confidence: 97%
“…97 Several other ligand-receptor combinations appear to positively influence keratinocyte migration and proliferation in vitro. 98,99 In vivo studies in CXCL11…”
Section: Remodeling Phasementioning
confidence: 99%